2010
DOI: 10.1159/000281879
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Arterial and Venous Blood Gases and the Effects of Analysis Delay and Air Contamination on Arterial Samples in Patients with Chronic Obstructive Pulmonary Disease and Healthy Controls

Abstract: Background: Arterial blood gases (ABGs) are often sampled incorrectly, leading to a ‘mixed’ or venous sample. Delays in analysis and air contamination are common. Objectives: We measured the effects of these errors in patients with chronic obstructive pulmonary disease (COPD) exacerbations and controls. Methods: Arterial and venous samples were analyzed from 30 patients with COPD exacerbation and 30 controls. Venous samples were analysed immediately and arterial samples separated into non-air-contaminated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…, n.b. figure analysis excludes O'Connor, due to incomplete data). Heterogeneity was statistically significant; the I 2 of 99.6% showed that most variability was across studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…, n.b. figure analysis excludes O'Connor, due to incomplete data). Heterogeneity was statistically significant; the I 2 of 99.6% showed that most variability was across studies.…”
Section: Resultsmentioning
confidence: 99%
“…, n.b. figure analysis excludes O'Connor). The difference between the venous and arterial PO 2 was very large.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Low pO 2 values can be found in patients with respiratory diseases or at high altitude (e.g., hiking, mountaineering, during air travel). [14][15][16][17][18][19] Increased pO 2 values can occur in patients requiring artificial respiration. 9,11,20 In this study, at ''high'' pO 2 values the GOD systems showed a negative bias for the measurement results compared with those at pO 2 values approximately 70 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased pO 2 levels can be expected, e.g., during long-distance flights or in patients with respiratory diseases. [9][10][11][12][13] In addition, for many GOx systems, detailed information, i.e., the pO 2 range in which the system operates well, is not provided in the manufacturers' labeling.…”
Section: Introductionmentioning
confidence: 99%